Dynamization Analysis of Capital Inflow, Credit Allocation, and Banking Performance using Panel Vector Autoregressive - Ekananda, Mahjus (Universitas Muhammadiyah Yogyakarta, 2022)
The direction of globalization and the integration of the financial system continue to increase, in line with the increasing capital flows, which is the focus of discussion in this research. This study applies panel data analysis to analyze banking behavior in order to improve its performance. The analysis uses panel data from 1991 to 2020 in 39 countries. Return on Equity (ROE) as a measure of the success of banking operations is determined by various interrelated factors. One of the variables closely related to banking performance is the share of non-financial business loans, the share of capital inflows entering the banking sector, and the share of capital inflows entering the non-bank sector. Economic variables that support good banking performance are GDP growth, bank concentration, inflation, leverage, and bank efficiency. This article applies a Panel Vector Autoregressive to capture the dynamization, and heterogeneity. The most exciting results were obtained by dividing the sample into subgroups, which helped the researcher understand each regime's different roles and transmissions. The changes in capital inflows to the non-bank sector will significantly reduce ROE and increase leverage for the next five periods. The results of the study imply that nowadays, bank managers should be aware while the changes in capital inflows change very quickly. Bank managers in countries with high capital inflows must always be aware of changes in capital inflows to the non-bank sector—steps to bank management by diversifying sources of funds efficiently from other parties in the transmission of credit channel.